1998
DOI: 10.1021/je980106y
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension of Binary Mixtures of Water +N-Methyldiethanolamine and Ternary Mixtures of This Amine and Water with Monoethanolamine, Diethanolamine, and 2-Amino-2-methyl-1-propanol from 25 to 50 °C

Abstract: The surface tension of aqueous solutions of N-methyldiethanolamine and diethanolamine + N-methyldiethanolamine, monoethanolamine + N-methyldiethanolamine and 2-amino-2-methyl-1-propanol + N-methyldiethanolamine was measured at temperatures from 25 °C to 50 °C. For binary mixtures the concentration range was 0−50 mass % N-methyldiethanolamine, and for the tertiary mixtures the concentration range for each amine was 0−50 mass %. The experimental values were correlated with temperature and mole fraction. The maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 14 publications
9
54
1
Order By: Relevance
“…In order to obtain the interfacial tension of water/n-alkane interface, we first calculated the surface tensions (  ) of water/ vapor and n-alkane/vapor surfaces which consist of the same number of water or n-alkane molecules as used in each phase of the water/n-alkane interface. The calculated surface tension of water/vapor at 300 K was 70.57 ± 0.51 mN/m, which agrees very well with the experimental value 71.72 mN/m [28,29]. The calculated and experimental surface tensions for n-alkane/vapor are shown in Table 2.…”
Section: Interfacial Tensionsupporting
confidence: 80%
“…In order to obtain the interfacial tension of water/n-alkane interface, we first calculated the surface tensions (  ) of water/ vapor and n-alkane/vapor surfaces which consist of the same number of water or n-alkane molecules as used in each phase of the water/n-alkane interface. The calculated surface tension of water/vapor at 300 K was 70.57 ± 0.51 mN/m, which agrees very well with the experimental value 71.72 mN/m [28,29]. The calculated and experimental surface tensions for n-alkane/vapor are shown in Table 2.…”
Section: Interfacial Tensionsupporting
confidence: 80%
“…x ij 2 + y ij of water or decane molecules as used in each phase of the decane-water and decane-surfactant-water interfaces. The calculated interfacial tension at 300 K was 21.77 ( 2.31 dyn/ cm for the decane-vacuum interface and 70.94 ( 2.25 dyn/ cm for the water-vacuum interface, which agree very well with the experimental values (23.20 dyn/cm for the decane 91 and 71.72 dyn/cm for the water 72,92 ). In addition, the interfacial tension of the decane-water interface without a surfactant was 54.70 ( 3.62 dyn/cm, which is also in good agreement with the experimental value (51.72 dyn/cm).…”
Section: Ife )supporting
confidence: 81%
“…Our research group has observed this behavior for other binary systems. 7,11 In previous papers by our group and other authors, 8,13 the surface tension versus temperature data have been fit with a linear regression employing eq 4.…”
Section: Effect Of Compositionmentioning
confidence: 99%